Cat Kid comic club. Influencers - Pilkey, Dav, 1966- (New York, NY : Graphix, an imprint of Scholastic, 2023)
The Cat Kid Comic Club is in crisis! After learning that one of their comics will be published, the baby frogs are filled with anxiety and doubt. How will they get their creative groove back? Will Naomi or Melvin emerge as a leader? Will Flippy convince them to finally straighten up and fly right?
3-6
GN510L
Keywords: Cats -- Comic books, strips, etc; Cats -- Juvenile fiction; Frogs -- Comic books, strips, etc; Frogs -- Juvenile fiction; Clubs -- Comic books, strips, etc; Clubs -- Juvenile fiction; Drawing -- Technique -- Comic books, strips, etc; Drawing -- Technique -- Juvenile fiction; Creative ability -- Comic books, strips, etc; Creative ability -- Juvenile fiction; Humorous stories; Cats -- Fiction; Frogs -- Fiction; Clubs -- Fiction; Drawing -- Technique -- Fiction; Creative ability -- Fiction; Humorous comics; Funny animal comics; Graphic novels; Comics (Graphic works)